Caesarean Section on Maternal Request (CDMR) - Patted, Shobhana (Recent Research in Science and Technology, 2011)
A maternal request for caesarean delivery in the absence of medical indication raises several ethical issues. Those who favour women’s autonomy in childbirth may advocate CDMR however at present there is no strong evidence to favour caesarean section over vaginal delivery in terms of both maternal and neonatal morbidity and mortality. Every effort must be made to reduce the incidence of caesarean on demand by focussing on providing correct information on the relative risk and benefit associated with vaginal delivery VS caesarean section.